Bi-nasal sectors of ganglion cells complex and visual evoked potential amplitudes as biomarkers in pituitary macroadenoma management - Hernández-Echevarría, Odelaisys; Cuétara-Lugo, Elizabeth Bárbara; Pérez-Benítez, Mario Jesús; González-Gómez, Julio César; González-Diez, Héctor Raúl; Mendoza-Santiesteban, Carlos E. (Frontiers in Integrative Neuroscience, 2022)
The study was aimed to evaluate the retinal ganglion cell structure using OCT and the visual pathway function employing VEP in the diagnosis and monitoring of patients with PMA. A descriptive, cross-sectional and longitudinal study (3 and 12 months follow-up) was conducted on forty-two PMA patients. Thirty five age-matched healthy controls were used in the cross-sectional one. Full neuro-ophthalmological evaluation (structural and functional) was carried out including global and segmented RNFL/GCC analysis by OCT and VEP P100 amplitude and latency. Statistical data analysis was conducted with R version 3.6.3 and Python version 3.8. Associations were evaluated using Spearman correlations. VEP amplitudes sensitivities’ were 0.999 and global GCC and its bi-nasal sectors thickness’ specificities were 0.999. Bi-nasal of GCC had the highest diagnostic value (AUC = 0.923). Significant associations were found between global GCC and its bi-nasal sectors with VEP amplitude (Oz, 12’) (rho ˃ 0.7, p ˂ 0.01) and VF MD (rho ˃ 0.5, p ˂ 0.01); at three months. VEP amplitude and VF MD (rho ˃ 0.6, p ˂ 0.01), at 12 months had also a moderate association. Pre-surgical values of global and bi-nasal of GCC and VEP amplitude can predict post-surgically VF MD and VEP amplitude (Oz, 12’) at three months with r2 ˃ 0.5. Bi-nasal sectors of GCC and VEP P100 amplitude are efficient biomarkers of visual pathway damage for PMA patients’ management. Pre-surgical values of global GCC, bi-nasal sector of GCC, and VEP amplitude could help to predict the restoration of parvocellular pathway traffic after decompression.